The Design of Moodle-Based English Language Learning Environments (Case Study of Indonesian Higher Education) - Rizky Eka Prasetya (ELT Worldwide: Journal of English Language Teaching, 2021)
Integrating English learning content enhance complexity and unconventional demands challenge lecturers in Higher Education. The study investigates and determines an English learning course design through Moodle, the most suitable approach that develops an online environment’s essential language learners’ accomplishment outcomes. The study was conducted with the qualitative approach with a case study research design. The thirty-eight lecturers generate as respondents from Higher Education in the Jakarta area. The result has found that Moodle could implement the demands-complexity of English language learning in the electronic ecosystem. The English course should have obtained attention or engagement with familiarize, encourage, fulfill, evaluate, and understand actual content material integrated Moodle feature.  The Moodle-based designer must develop topological technologies to request the particular necessities of learners needs. Moodle is not fundamentally constructed as a mechanism concerning language learning, and it should have been noticed that the electronic model was not a flawless online learning system for the English educational process. Nonetheless, it presents various resources and excellent learning designs. It frequently engaged learners’ and lecturers’ adverse responses to the acquiring of English as a foreign language. Technical problems and educational challenges should not be neglected while utilizing Moodle program in the electronic ecosystem